Efektivitas Biaya Kualitas dalam Rangka Menekan Produk Rusak pada PT. Perkebunan Nusantara XI PG. Redjosarie (Jurnal Manajemen dan Organisasi, 2020)
Company implements quality cost to prevent and surpress the existence of damaged products. This research is conducted at PT. Perkebunan Nusantara XI Redjosarie Sugar Factory that produces white crystal sugar. Quality costs applied by Redjosarie Sugar Factory consists of prevention cost and appraisal cost. The aim of this study is to identify the condition of damaged products and causatife factors of damaged products, analyze the things that affect the effectiveness of quality cost in order to surpress the damaged products. The result shows the highest percentage of damaged products compared to the total production showing a figure 0,0115 percent and the factors causing the damaged products at Redjosarie Sugar Factory are man factor, machine factor, material factor, method factor and modal factor. While the implementation of cost quality in surpessing damaged products is not effective because the percentage index of quality cost compared to total sales shows a figure above 2,5 percent.